Research on public opinion guidance mechanism of major public health emergencies under new media environment - Yang, Xiao (The Journal of Medicine, Humanity and Media, 2024)
Major public health emergencies have attracted widespread attention from the public due to their urgency, large impact range and serious damage consequences. With the constant change of network technology and media environment, the pattern of public opinion also presents new characteristics, and the guidance of public opinion on major public health emergencies is even more difficult for our government and media. During the 2020 COVID-19 epidemic, the sudden outbreak of the epidemic is a major test for China’s government and media to guide public opinion in a state of crisis. Therefore, it is necessary to establish a sound public opinion guidance mechanism in public health emergencies.